Evaluating the Timeliness of Enteric Disease Surveillance in British Columbia, Canada, 2012-13. (1st June 2017) - Galanis, Eleni; Taylor, Marsha; Romanowski, Kamila; Bitzikos, Olga; Jeyes, Jennifer; Nowakowski, Craig; Stone, Jason; Murti, Michelle; Paccagnella, Ana; Forsting, Sara; Li, Sophie; Hoang, Linda
Abstract : Timely surveillance of enteric diseases is necessary to identify and control cases and outbreaks. Our objective was to evaluate the timeliness of enteric disease surveillance in British Columbia, Canada, compare these results to other settings, and recommend improvements. In 2012 and 2013, information was collected from case report forms and laboratory information systems on 2615 Salmonella, shigatoxin-producing E. coli, Shigella, and Listeria infections. Twelve date variables representing the surveillance process from onset of symptoms to case interview and final laboratory results were collected, and intervals were measured. The median time from onset of symptoms to reporting subtyping results to BC epidemiologists was 26–36 days and from onset of symptoms to case interview was 12–14 days. Our findings were comparable to the international literature except for a longer time (up to 29 day difference) to reporting of PFGE results to epidemiologists in BC. Such a delay may impact our ability to identify and solve outbreaks. Several process and system changes were implemented which should improve the timeliness of enteric disease surveillance.